Exploring The Purchase Intention Among Older Consumers: Fenjiu as a Case in Shanxi Province, China - Hu, Chaojie; Jiang, Songyu (Jurnal Toursci, 2025)
Background. China’s demographic transition into an aging society has reshaped the country’s consumer landscape, positioning older adults as a strategically vital market segment. This demographic shift is particularly consequential in the liquor industry, where traditional Chinese liquors hold deep cultural, ceremonial, and social significance. Aims. (1) to explore the influence of functional value, social value, emotional value, Epistemic value, and conditional value on consumer satisfaction; (2) to analyze the influence of functional value, social value, emotional value, epistemic value, and conditional value on consumers' intention to buy Fenjiu. (3) to verify the mediating role of consumer satisfaction. Methods. This study used a quantitative research method, surveyed 412 Chinese elderly people who had experience in purchasing Fenjiu, and then analyzed the data using a structural equation model. Result. Functional, social, emotional, and epistemic values all exert significant positive effects on consumer satisfaction, while conditional value fails to reach statistical significance. Social, epistemic, functional, and conditional values significantly predict purchase intention, while emotional value is not significant. Satisfaction significantly and positively predicts purchase intention and serves as a stable mediator in the paths of functional, social, emotional, and epistemic values, while the path from conditional value does not reach significance.. Conclusion. The findings highlight the importance of emotional and epistemic engagement in aging consumers’ liquor consumption and offer strategic insights for culturally rooted brand marketing